Development and Validation of Analysis Methods for Retinoids, Arbutin, Nicotinamide in HPLC Cosmetics - Nuraini, Ika; Iswandi; Supriyadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
There are many skin lightening cosmetics on the market. Active ingredients commonly used in skin lightening cosmetics are arbutin, nicotinamide and retinoids. The purpose of this study is to determine the best conditions of HPLC that can separate several compounds and ensure the validity of the method. HPLC system that can separate several analytes, validating the method with parameters such as selectivity, linearity with a range of 25-150 ppm, LOD, LOQ, accuracy with simulation methods with 100% concentration is 100 ppm, precision with simulation methods at a concentration of 50 ppm. After the method is valid, the determination of levels is carried out on the sample. Results of this study are the best conditions that can be used to separate several analyte compounds using a KCKT system with a UV detector at a wavelength of 227 nm, a flow rate of 1ml/min and using isocratic elution with a mobile phase composition of WFI: acetonitrile: ethanol (10:65:25), the method used has been tested valid with a selectivity value of 1,590 and 4,028, with linearity values for arbutin, nicotinamide, retinoid is 0,999; 0,9980; 0,997 respectively, LOD value 7,8 ppm, LOQ 26,1 ppm, %recovery 96,863, %RSD 3,167